Patients’ knowledge, attitudes, and practices regarding lifestyle related dry eye - Ke Song; Shanshan Ye; Shujiao Li; Ningling Wu; Zefeng Kang (Scientific Reports)
Abstract Rising incidences of dry eye, often attributed to modern lifestyle and environmental factors, highlight the need for knowledge, attitudes, and practices (KAP) studies to inform tailored interventions. This study evaluated patients’ KAP concerning lifestyle-related dry eye at the Ophthalmology Hospital of the China Academy of Chinese Medical Sciences from July 1 to July 26, 2024. A self-designed questionnaire was used to gather demographic data and assess KAP scores, yielding 556 valid responses (98.93%). Among participants, 342 (61.51%) were female, with a mean age of 39.26 ± 13.56 years. Mean KAP scores were 7.44 ± 4.65 (knowledge), 35.20 ± 4.10 (attitude), and 35.77 ± 6.15 (practice). Mediation analysis indicated direct influences of age and familial dry eye history on knowledge, with knowledge impacting attitude, and various factors influencing practice. While patients exhibited limited knowledge, they generally held positive attitudes and engaged in proactive practices. Enhancing patient education on lifestyle factors related to dry eye is essential to boost knowledge and foster effective prevention and management strategies.